Cowboy Night Before Christmas - Rice, James; 1934- (Gretna, La., 1990)
When Santa's reindeer abandon their job in the midst of a Texas storm, he enlists the help of two lonely cowpokes so that he can finish his Christmas Eve rounds.
Keywords: Stories in rhyme; Fiction; Christmas; Fiction; Cowboys; Santa Claus; Fiction; Texas; Fiction